Analysis of IT Helpdesk Ticketing System on Alibaba Cloud Elastic Compute Service - Akbar, Putra Wahyudi; Fatoni, Fatoni; Zuhriyadi, Ilman; Mukti, Aan Restu (INOVTEK Polbeng - Seri Informatika, 2024)
The IT Helpdesk Ticketing System is an application developed for managing IT technical complaints at Siti Khadijah Islamic Hospital, Palembang. The hospital faces issues due to the absence of a system to record and track complaints from various units to the IT division in an organized manner. To address this, the IT Helpdesk Ticketing System web application was created to facilitate reporting IT problems and assist the IT division in monitoring and addressing reports. This application is deployed on Alibaba Cloud ECS (Elastic Compute Service), chosen for its flexible virtual server performance. The study will analyze Alibaba Cloud ECS’s effectiveness in supporting the IT Helpdesk application. Blackbox testing results indicate that the application meets all specified functional requirements, with features performing as expected and no functional errors. Apache JMeter testing on Alibaba Cloud ECS showed an average throughput of 1.6 Mbps, a sample response time of 25,991.5 ms, and latency of 74,576 ms. Average utilization results are CPU Utilization at 96.97%, Memory at 87.11%, disk read at 7.86 MB/s, and write at 3.83 MB/s. The study employs the NDLC (Network Development Life Cycle) and web engineering methods.